Sequence-Based Analysis of Protein Energy Landscapes Reveals Nonuniform Thermal Adaptation within the Proteome - Gu, Jenny (Oxford University Press, 2009)
Thermal adaptation of individual proteins is often achieved through modulating protein stability, with proteins that are adapted to extreme cold environments having increased conformational flexibility when brought to mesophilic conditions. Conversely, proteins adapted to higher temperatures appear less dynamic and are found to be much more stable against thermal denaturation than their mesophilic counterparts. According to the current paradigm, the adaptation of an organism for survival at higher or lower temperatures is facilitated by the adaptation of the component proteins. We note, however, that these observations have been carried out on relatively few proteins. The extent to which the conformational stabilities of all members of the proteome have been modulated for thermal adaptation remains unclear, with no direct experimental strategies to address this issue. Adapted extremophilies are likely to use a multitude of molecular and biophysical strategies for survival and, therefore, evolution of specific biophysical properties of proteins for optimal function may not be necessary for all proteins in the proteome. Using a sequence-based predictor of protein stability, eScape, an in silico examination of several extremophilic proteomes shows a correlation between the collective stability of the proteins and the thermal range of survival for the organism as expected. Unexpectedly, however, the analysis shows that protein thermostability is modified to different extents across the proteome and depends on the functional role for which the protein is involved. Identification of these differences provides unique opportunities to study interdependence within the proteome as well as the role that the proteome plays in the process of evolutionary thermal adaptation.